IMPROVED PERFORMANCE OF AGRICULTURAL EXTENSION AGENTS WITH INFRASTRUCTURAL FACILITIES AND TRAINING THROUGH JOB SATISFACTION - Mumakinah, Tri; Setiawan, Margono; Irawanto, Dodi Wirawan (Jurnal Aplikasi Manajemen, 2020)
The research aims to find out whether there is any significant correlation between infrastructural facilities, training, and performance of agricultural extension agents, mediated by job satisfaction in the Agricultural Extension Office in Malang Raya. This research used a qualitative method. The data was collected using a questionnaire, and the technique used in taking the sample was saturation sampling. The sample comprised all agricultural extension agents who were also civil servants, who had working experience of a minimum of one year, and worked at the district-level agricultural extension office in Malang. The total respondents were 145 people. The data analysis was conducted using Partial Least Square (PLS) Method by employing the 3.0 SmartPLS program. The research results showed that all the hypotheses put forward were corroborated except the one dealing with infrastructural facilities. Infrastructural facilities did not have a significant effect on job satisfaction because their availability had not been considerably capitalized on in carrying out the agricultural extension. Besides, it was found that job satisfaction did not mediate the influence of infrastructure on the performance of the extension agents. Recommendations for research in the future on similar topics may use an additional comparison between the satisfaction of expert and skilled agricultural extension agents, and the research method may be developed using qualitative methods.